جمع التكسير في كتاب الإملاء المختصر في شرح غريب السير لأبي ذر مصعب الخشني "ت. 604 هـ." - محمد، إيهاب أحمد; محمود، حسين نوري (جامعة تكريت - كلية التربية للبنات, 2024)
يعد أبو ذر مصعب الخشني من أبرز علماء اللغة في القرن السابع الهجري، وتسعى هذه الدراسة إلى إبراز جهوده اللغوية لا سيما في علم الصرف، وتسليط الضوء على نماذج أوردها من موضوع (جمع التكسير) في (كتاب الإملاء المختصر في شرح غريب السير لأبي ذر الخشني الأندلسي (ت 604هـ)، إذ يهدف البحث إلى التعريف بأنواع الجمع الوارد في الكتاب، والوقوف على الأمثلة التي أوردها الخشني في إملائه ذاكرا آراء علماء اللغة من القدماء والمحدثين ومحللا إياها. وتوصل الباحث إلى أن الخشني كان عميد علوم العربية في عصره فقد قيل فيه: حامل لواء العربية في الأندلس، وكذلك أولى الخشني موضوع جمع التكسير اهتماما خاصا؛ وذلك بسبب منهجه في الكتاب فهو أقرب إلى منهج المعجميين، فنراه يذكر الكلمة، وأصلها، ودلالتها، وجمعها، وغير ذلك من المشتقات التي تشتق منها اللفظة. Abu Dharm Musab Al-Khushani is considered one of the most prominent linguists of the seventh century AH. This study seeks to highlight the efforts of an Andalusian linguist, and to shed light on his morphological efforts through examples on the subject plural of takasir in the book Al-Imlah Al-Mukhtasar fi Sharh Gharib Al-Sir by Abu Dhar Al Khushni Al-Andalusi (d. 604 AH). The research aims to introduce the types of plurals mentioned in the book, and to find examples of what Al-Khushni mentioned in his dictation, citing the opinions of ancient linguists. And the Modern linguists in the examples you provided. The researcher concluded that Al-Khushani was the dean of Arabic sciences in his time. It was said about him: The standard-bearer of Arabic in Andalusia. Al-Khushani also paid special attention to the subject of the plural of takasir. This is because his approach in the book is closer to the approach of lexicographers, so we see him mentioning the word, its origin, connotation, plural, and other derivatives from which the word is derived.
Keywords: علم الصرف -- صيغ الجموع -- القواعد اللغوية -- الخشني، مصعب بن محمد بن مسعود بن عبدالله، ت. 604 هـ